Hands-On Financial Modeling with Microsoft Excel 2019 : Build Practical Models for Forecasting, Valuation, Trading, and Growth Analysis Using Excel 2019. - Oluwa, Shmuel (Packt Publishing, Limited, 2019)
This book aims to provide a gateway to financial modeling through easy to follow examples in Excel 2019. It will explore the process of modeling starting from a thorough understanding of the project to gathering historical information and arriving at assumptions. Good modeling practices are emphasized and demonstrated throughout the book.